THE DOWNSIDE OF PERFORMING ENVIRONMENTALISM: CORE REASONS FOR THE SOCIAL DISCREDITING OF FAKE ECO-TRAVELERS (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores the phenomenon of “performative eco-tourism” - the negative consequences of portraying oneself as an environmentalist without genuine commitment - and the core reasons for the social discrediting of “fake” eco-travelers. The study examines the shift from authentic nature conservation to image-building on social media and the subsequent social backlash that occurs when inauthenticity is exposed. The paper identifies key factors leading to the discrediting of such travelers, including moral inconsistency, virtue signaling, and growing audience skepticism. The findings highlight how performative environmentalism can damage a person's reputation and hinder genuine sustainability efforts.
Keywords: Fake eco-travelers, performative environmentalism, social discrediting, social media, inauthenticity, sustainable tourism, social criticism.